2019
DOI: 10.1155/2019/4793764
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Risk Factors for Spontaneous Closure of Idiopathic Full-Thickness Macular Hole

Abstract: Idiopathic full-thickness macular hole is a severe visual impairment disease. Pars plana vitrectomy remains the primary treatment option for idiopathic full-thickness macular holes, and over 90% idiopathic full-thickness macular holes are closed by vitrectomy surgery. However, the full-thickness macular hole may close spontaneously, with a good visual acuity progress. Since recent studies are small-sample studies and case reports, the characteristics for spontaneous closure of idiopathic full-thickness macular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 33 publications
(31 reference statements)
2
35
0
2
Order By: Relevance
“…[44] According to a recent literature review of 58 spontaneously resolved IMHs, the incidence of spontaneous closure is 4-11.5%. [43] MH closure was observed for all stages, though it was less frequent with more advanced stages. Hole diameter was documented in 50 cases.…”
Section: Observation and Spontaneous Closurementioning
confidence: 83%
See 1 more Smart Citation
“…[44] According to a recent literature review of 58 spontaneously resolved IMHs, the incidence of spontaneous closure is 4-11.5%. [43] MH closure was observed for all stages, though it was less frequent with more advanced stages. Hole diameter was documented in 50 cases.…”
Section: Observation and Spontaneous Closurementioning
confidence: 83%
“…Yet, some VMT cases or early FTMHs may spontaneously resolve. [43] Among eyes with VMT, about 60-70% will progress to FTMHs, while the remaining fraction will resolve spontaneously. [44] According to a recent literature review of 58 spontaneously resolved IMHs, the incidence of spontaneous closure is 4-11.5%.…”
Section: Observation and Spontaneous Closurementioning
confidence: 99%
“…This is longer than previous studies. [16][17][18][19][20][21][22][23][24][25] It has been reported that the IMHs with disease course more than 6 months is more di cult to close than that of less than 6 months. 11 Therefore, we did a subgroup analysis for those patients with a disease course longer than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters are also complex and di cult to calculate, limited their application values in busy real world clinical practice. [16][17][18][19] Based on our clinical experiences 11,20,[23][24][25][26] , we feel that the preoperative MH morphological characteristics are different between postoperative closed and unclosed stage III or IV IMHs. Thus we try to nd a method to quantitatively evaluate the morphological characteristics of preoperative MHs to predict the postoperative closure for stage III or IV IMHs.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation